Cu-Bi bimetallic catalyst for preparing acetaldehyde through ethanol dehydrogenation as well as preparation method and application of Cu-Bi bimetallic catalyst

By loading Cu and Bi on a SiC support, the Cu-Bi bimetallic catalyst solves the problems of insufficient acetaldehyde selectivity and stability in the process of ethanol dehydrogenation to acetaldehyde, achieving efficient and stable acetaldehyde production, which is suitable for industrial applications.

CN120662348APending Publication Date: 2025-09-19HUBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510793613.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-13
Publication Date
2025-09-19

AI Technical Summary

Technical Problem

Existing catalysts have problems such as poor acetaldehyde selectivity, low stability and short service life in the process of ethanol dehydrogenation to acetaldehyde, which makes it difficult to meet the needs of industrial production.

Method used

A Cu-Bi bimetallic heterogeneous catalyst is used. By loading Cu and Bi on a SiC carrier, combined with high-temperature activation, gradient ammonia evaporation and high-temperature calcination treatment, the distribution and synergistic effect of the active components are optimized, thereby improving the activity and stability of the catalyst.

Benefits of technology

The acetaldehyde selectivity and catalyst stability are significantly improved, the service life is extended, the requirements of industrial applications are met, and the preparation and use costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120662348A_ABST
    Figure CN120662348A_ABST
Patent Text Reader

Abstract

The invention discloses a Cu-Bi bimetallic heterogeneous catalyst for preparing acetaldehyde through ethanol dehydrogenation as well as a preparation method and application of the Cu-Bi bimetallic heterogeneous catalyst, and belongs to the technical field of chemical catalysis. According to the Cu-Bi bimetallic heterogeneous catalyst, SiC is used as a carrier, and active components Cu and Bi are loaded; wherein the loading amount of Cu is 3-15% of the total mass of the catalyst, the loading amount of Bi is 1-5% of the total mass of the catalyst, and the balance is the SiC carrier. The preparation method of the Cu-Bi bimetallic heterogeneous catalyst comprises the following steps: firstly, dipping the Cu-Bi bimetallic heterogeneous catalyst in a copper ammonia solution, and loading Cu on SiC through gradient ammonia distillation to obtain an intermediate; and dipping the intermediate in a bismuth salt aqueous solution, loading Bi, and carrying out high-temperature roasting to obtain the Cu-Bi bimetallic heterogeneous catalyst. The Cu-Bi bimetallic heterogeneous catalyst provided by the invention is good in stability, long in service life and high in acetaldehyde selectivity when being applied to preparation of acetaldehyde through direct dehydrogenation of ethanol, the yield of acetaldehyde can be remarkably improved, generation of by-products in the reaction process is reduced, the stability of the catalyst is also remarkably improved, the service life of the catalyst is also remarkably prolonged, and the catalyst is suitable for industrial production. And no obvious inactivation phenomenon occurs after continuous operation for 1500 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical catalysis, and particularly relates to a Cu-Bi bimetallic heterogeneous catalyst for preparing acetaldehyde by dehydrogenating ethanol, and a preparation method and application thereof. Background Art

[0002] Acetaldehyde is one of the important organic chemical intermediates, mainly used in the production of organic compounds such as pyridine and its derivatives, crotonaldehyde, hydroxypropionitrile, pentaerythritol, vinyl chloride monomer, ethylene dichloride, ether, and glycolic acid. It is also used as a basic raw material for the manufacture of fine organic chemical products such as fragrances, dyes, and medicines, and has important industrial application value.

[0003] Currently, the main synthetic routes for acetaldehyde include ethylene oxidation, acetylene hydration, acetic acid reduction, ethane oxidation, C3 / C4 alkane oxidation, and CH4 and CO synthesis. In recent years, direct ethanol dehydrogenation has been considered a promising future acetaldehyde production route. Ethanol, as a raw material, offers advantages such as high annual production, widespread distribution, and renewable availability. This method, with its simplicity, easy product separation, high atom economy, and minimal side reactions, has attracted significant research attention. While traditional catalyst systems used for direct ethanol dehydrogenation, such as Au, Ag, and Au-Cu alloys, exhibit promising performance, their high cost limits large-scale industrial application. For example, copper-based catalysts supported on oxides (e.g., SiO2 and Al2O3), while exhibiting high catalytic activity, suffer from poor selectivity for the main product, acetaldehyde, and suffer from low stability and susceptibility to deactivation, making them difficult to meet the requirements for efficient and stable catalysts in industrial production.

[0004] In recent years, some researchers have attempted to optimize the catalytic performance of copper-based catalysts by doping them with metal or non-metallic additives, thereby applying them to the catalytic dehydrogenation of ethanol to acetaldehyde. For example, when using gold-copper bimetallic catalysts for ethanol dehydrogenation at 220°C, their selectivity for acetaldehyde is low, ranging from 35% to 70%. When using Cu / ZrO2 catalysts for ethanol dehydrogenation, their selectivity for ethyl acetate reaches 81%, rather than the target product acetaldehyde, which clearly does not meet the requirements of the ethanol dehydrogenation reaction. Cu-mesoporous carbon, Cu / C / SiC, and Pt-Cu-zeolite catalysts, while exhibiting good catalytic activity, deactivate within tens of hours and exhibit poor stability, making them unsuitable for industrial production. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a Cu-Bi bimetallic heterogeneous catalyst for ethanol dehydrogenation to prepare acetaldehyde in view of the deficiencies in the above-mentioned prior art, which has high acetaldehyde selectivity and excellent catalytic stability and long service life.

[0006] The technical solution adopted by the present invention to solve the above-mentioned problems is: A Cu-Bi bimetallic heterogeneous catalyst for preparing acetaldehyde by dehydrogenation of ethanol comprises a SiC carrier, and active components Cu and Bi supported on the SiC carrier; wherein the active component Cu loading is 3-15% of the total mass of the catalyst, and the active component Bi loading is 1-5% of the total mass of the catalyst.

[0007] Furthermore, the particle size distribution of the SiC carrier is within a specific range, specifically 2-50 nm. Preferably, the particle size distribution of the SiC carrier is within a range of 10-30 nm.

[0008] Furthermore, the loading amount of the active component Cu is preferably 3-8% of the total mass of the catalyst, and the loading amount of the active component Bi is 1-3% of the total mass of the catalyst.

[0009] Furthermore, the total loading amount of the active components Cu and Bi is 6-10 wt % of the total mass of the catalyst, and the remainder is SiC support.

[0010] The present invention also provides a method for preparing the above-mentioned Cu-Bi bimetallic heterogeneous catalyst, comprising the following steps: (1) performing high-temperature activation treatment on the SiC carrier to obtain an activated SiC carrier; (2) completely immersing the SiC carrier obtained in step (1) in a copper ammonia solution for ultrasonic impregnation, and then performing gradient ammonia evaporation; after the ammonia evaporation is completed, filtering, washing and drying to obtain a Cu / SiC intermediate; (3) slowly adding a bismuth salt aqueous solution to the Cu / SiC intermediate obtained in step (2) so that the Cu / SiC intermediate is completely immersed in the bismuth salt aqueous solution and ultrasonically impregnated, and then filtering, washing and drying to obtain a bimetallic catalyst precursor; (4) The bimetallic catalyst precursor obtained in step (3) is calcined at a high temperature in an air atmosphere to obtain a Cu-Bi bimetallic heterogeneous catalyst.

[0011] Furthermore, in step (1), the SiC carrier is activated in an air atmosphere at a temperature of 400-600° C. for 1-10 hours.

[0012] Furthermore, in step (2), the copper ammonia solution is a copper ammonia complex solution formed by adding a copper salt to a solvent alcohol and dissolving it, then adding ammonia water to adjust the pH to 9-11 and continuously stirring. Specifically, the pH can be adjusted using ammonia water with a concentration of 20-30%; the copper salt is any one of soluble copper salts such as copper nitrate, copper chloride, and copper acetate, or a mixture of several of them in any proportion; and the solvent alcohol is any one of methanol, ethanol, isopropanol, butanol, or a mixture of several of them in any proportion.

[0013] Furthermore, in step (2), it is necessary to ensure that the copper ammonia solution can completely immerse the SiC carrier, and the ultrasonic immersion time is 1-10 hours.

[0014] Furthermore, in step (2), the specific process of gradient ammonia evaporation is as follows: after ultrasonic impregnation, the copper ammonia solution and the SiC carrier immersed in the copper ammonia solution are placed together in an environment with a temperature of 40-60°C to evaporate ammonia for 1.5-2.5 hours, and then the temperature is raised to 75-85°C at a rate of 1-3°C / min, and ammonia evaporation is continued for 2-4 hours until the pH value of the copper ammonia solution is less than 8, and the ammonia evaporation is completed.

[0015] Furthermore, in step (3), the concentration of bismuth ions in the bismuth salt aqueous solution is 0.01-0.06 mol / L, and the ultrasonic immersion time is 3-5 hours. Specifically, the bismuth salt is any one of soluble bismuth salts such as bismuth nitrate and bismuth chloride, or a mixture of several of them in any proportion.

[0016] Furthermore, in step (4), the specific process of high-temperature calcination is: the bimetallic catalyst precursor is calcined in an air atmosphere at a calcination temperature of 300-500°C for 4-6 hours. Preferably, the high-temperature calcination is performed in a muffle furnace at a heating rate of 2°C / min to the calcination temperature.

[0017] The present invention discloses a Cu-Bi bimetallic heterogeneous catalyst for use in ethanol dehydrogenation to produce acetaldehyde. The specific application method comprises: loading the Cu-Bi bimetallic heterogeneous catalyst into a fixed-bed reactor and reducing it in a mixed atmosphere of H2 and an inert gas at a temperature of 200-550°C for 2-8 hours to obtain an activated catalyst; then, vaporizing ethanol and carrying it in a carrier gas into a solid-phase bed reactor under atmospheric pressure and a temperature of 200-350°C, where it is dehydrogenated to produce acetaldehyde under the action of the activated catalyst. The carrier gas is an inert gas that does not chemically react with the catalyst, ethanol, or acetaldehyde.

[0018] Furthermore, the reducing atmosphere adopts a H2 / N2 mixed gas, and the volume ratio of H2 to N2 is 1:(8-10).

[0019] Compared with the prior art, the technical effects of the present invention are as follows: 1. The Cu-Bi bimetallic heterogeneous catalyst for ethanol dehydrogenation to acetaldehyde provided by the present invention has high acetaldehyde selectivity, can significantly improve the acetaldehyde yield, and reduce the formation of by-products during the reaction. In addition, the stability and service life of the catalyst are also significantly improved, and no obvious deactivation is observed after 1500 hours of continuous operation.

[0020] 2. In the process of preparing the Cu-Bi bimetallic heterogeneous catalyst of the present invention, the SiC support is first treated at high temperature to remove surface impurities and increase more defect sites. Then, gradient ammonia evaporation is used to ensure that the active component Cu is highly dispersed on the SiC support. This not only improves the utilization rate of the Cu active sites and promotes the diffusion, adsorption, decomposition and desorption of molecular reactants, thereby maintaining high catalytic activity, but also effectively inhibits the agglomeration and sintering of Cu particles during the reaction, thereby extending the service life of the catalyst. Then, an inorganic bismuth salt is introduced as an auxiliary agent to regulate the loading amount of the Cu and Bi bimetallic active components on the SiC support and optimize the synergistic effect between the copper-bismuth bimetallic active phases. This ensures that the activity and catalytic efficiency of the catalyst are improved while also enhancing the stability of the catalyst and effectively extending its service life, so that the catalyst can better meet the needs of industrial applications.

[0021] 3. The catalyst provided by the present invention has obvious advantages in terms of preparation and use costs, and the preparation conditions are mild and the synthesis steps are easy to control. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a transmission electron microscope (TEM) image of the Cu-Bi bimetallic heterogeneous catalyst prepared in Example 1.

[0023] Figure 2 This is a transmission electron microscope (HRTEM) image of the Cu-Bi bimetallic heterogeneous catalyst prepared in Example 1.

[0024] Figure 3 This is the elemental analysis diagram of the Cu-Bi bimetallic heterogeneous catalyst prepared in Example 1.

[0025] Figure 4 It is the XRD spectrum of the catalyst of Example 1, the catalyst of Comparative Example 1 and the SiC carrier after calcination.

[0026] Figure 5 This is a comparison chart of the catalytic activities of the catalysts prepared in Example 1 and Comparative Example 1 within 1500 hours. DETAILED DESCRIPTION

[0027] In order to better understand the present invention, the content of the present invention is further illustrated below in conjunction with examples, but the present invention is not limited to the following examples.

[0028] In the examples, if the specific conditions are not specified, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer; the reagents or instruments used without specifying the manufacturer are conventional products that can be purchased from the market.

[0029] In the following examples, the particle size distribution of the carrier SiC is 10-30 nm.

[0030] In the following examples and comparative examples, the catalyst is abbreviated as mCu-nBi / SiC, where m represents the Cu loading as a percentage of the total catalyst mass × 100 (rounded to the integer); n represents the Bi loading as a percentage of the total catalyst mass × 100 (rounded to the integer); in Comparative Example 1, n is 0. The loadings used in this invention refer to the theoretical loadings.

[0031] Example 1 A Cu-Bi bimetallic heterogeneous catalyst comprises a SiC support, and active components Cu and Bi supported on the SiC support. The active component Cu is loaded at 5% of the total catalyst mass, the active component Bi is loaded at 1% of the total catalyst mass, and the remainder is the SiC support. This catalyst is abbreviated as a 5Cu-1Bi / SiC catalyst.

[0032] The preparation method of the 5Cu-1Bi / SiC catalyst described in this embodiment has the following specific steps: (1) Weigh 7.5 g of copper acetate and dissolve it in 100 ml of anhydrous ethanol. Stir at room temperature for 3 h. Then add 50 ml of 25% ammonia water and adjust the pH value of the system to 10. Maintain the temperature at 30 °C and continue stirring for 2 h. At this time, the solution gradually turns dark blue, which is a copper ammonia solution. At the same time, 50.0 g of silicon carbide was placed in a muffle furnace and oxidized at 400° C. in an air atmosphere for 4 h to obtain an activated SiC carrier.

[0033] (2) The activated SiC support was added to the copper ammonia solution to ensure that the support was completely immersed. The resulting mixed system was ultrasonically treated for 4 hours to promote the uniform dispersion of the copper ammonia complex on the support surface. The ultrasonically treated copper ammonia solution and the SiC support immersed in the copper ammonia solution were then placed in a 50°C oil bath and ammonia was evaporated for 2 hours. The system temperature was then raised to 80°C at a heating rate of 2°C / min and ammonia was evaporated for 3 hours until the pH of the system was less than 8. After the ammonia evaporation was completed, the product was washed with 50 ml of ethanol to remove excess solutes and dried at 80°C overnight to obtain a Cu / SiC intermediate.

[0034] (3) Weigh 1.2 g of bismuth nitrate and dissolve it in 100 ml of deionized water to obtain a 0.03 mol / L aqueous solution of bismuth nitrate. Then, add the aqueous solution of bismuth nitrate dropwise to the Cu / SiC intermediate obtained in step (2), ensuring that the intermediate is completely immersed in the solution. After ultrasonic immersion for 2 h, filter out the solid product, wash with 30 ml of ethanol, and dry in a vacuum drying oven at 60°C for 6 h to obtain a bimetallic catalyst precursor.

[0035] (4) The bimetallic catalyst precursor was placed in an air atmosphere, heated to 450°C at a rate of 2°C / min, and calcined for 3 h to obtain a 5Cu-1Bi / SiC catalyst, i.e., the Cu-Bi bimetallic heterogeneous catalyst described in this embodiment.

[0036] The following is an explanation of the theoretical loading capacity of 5% Cu in this embodiment, and the formula involved is as follows:

[0037]

[0038] Where m represents mass, M represents molar mass, and n represents the amount of substance. Based on m(SiC) = 50 g and M(Cu) = 63.55 g / mol, we calculate m(Cu) = 2.63 g, which represents an amount of substance of 0.0414 mol. In this example, the copper salt used is copper acetate, with M(copper acetate) = 181.63 g / mol, requiring approximately 7.5 g of copper acetate. The above formula for calculating the theoretical loading also applies to bismuth salt loading. The amounts of copper and bismuth salts used in other examples and comparative examples were calculated using the same method.

[0039] Depend on Figure 1 、 Figure 2 It can be seen that in the Cu-Bi bimetallic heterogeneous catalyst prepared in Example 1, the particle size of its carrier SiC is in the range of 10-30 nm, and the active components Cu and Bi are evenly distributed on the carrier surface, achieving high dispersion of the bimetallic active components and improving the catalyst activity.

[0040] Figure 3 In the figure, the left side is the element distribution of the active component Cu in the Cu-Bi bimetallic heterogeneous catalyst prepared in Example 1, and the right side is the element distribution of the active metal Bi. It can be seen that Cu is evenly distributed on the surface of the carrier SiC, and the presence of Bi plays a role in dispersing Cu particles, which can effectively inhibit the agglomeration of the active components and extend the service life of the catalyst.

[0041] Depend on Figure 4 It can be seen that the main active component CuO of the catalyst prepared in Comparative Example 1 has characteristic diffraction peaks at diffraction angles of 2θ=35.5° and 2θ=38.6°; the catalyst prepared in Example 1 successfully grows Cu and Bi oxides, and the surface active components Cu and Bi are successfully loaded, among which the Bi oxide has a corresponding characteristic diffraction peak at a diffraction angle of 2θ=27.4°.

[0042] Example 2-12 According to the preparation steps of Example 1, the types and amounts of copper salt and bismuth salt were adjusted to obtain a series of catalysts of Examples 2-12, as shown in Table 1. The following comparative examples are provided for comparison with the examples to illustrate the effects of different preparation methods on the catalyst activity.

[0043] Comparative Example 1 5Cu / SiC was prepared by impregnation method. The specific preparation process is as follows: Weigh 8.9 g of copper nitrate, dissolve it in 100 ml of water, add 50.0 g of silicon carbide, and stir at room temperature for 12 hours. The resulting mixed turbid liquid is filtered and washed with water until neutral; the filter residue is dried at 80°C overnight and calcined at 500°C in air atmosphere for 3 hours to obtain a 5Cu / SiC catalyst.

[0044] Comparative Example 2 The 5Cu-1Bi / SiC-A catalyst was prepared by impregnation method. The specific preparation process is as follows: 8.9 g of copper nitrate and 1.2 g of bismuth nitrate were weighed and dissolved in 200 ml of water. 50.0 g of silicon carbide was added and stirred at room temperature for 12 hours. The resulting mixed turbid liquid was filtered and washed with water until neutral. The filter residue was dried at 80°C overnight and calcined in air at 500°C for 3 hours to obtain a 5Cu-1Bi / SiC-A catalyst.

[0045] Comparative Example 3 The 5Cu-1Bi / SiC-B catalyst was prepared by co-precipitation method. The specific preparation steps are as follows: 8.9 g of copper nitrate and 1.2 g of bismuth nitrate were weighed and dissolved in 300 ml of water. 50.0 g of silicon carbide was added, and the pH of the system was adjusted to 10 with a 3 mol / L aqueous solution of NaOH. The resulting mixed solution was stirred at 80°C for 2 h, filtered, and washed with water until neutral. The filter residue was dried at 80°C overnight and then calcined at 500°C in an air atmosphere for 3 h to obtain a 5Cu-1Bi / SiC-B catalyst.

[0046] Application Examples The catalysts prepared in the above examples and comparative examples were used to dehydrogenate ethanol to produce acetaldehyde. The specific method is as follows: 30 ml of catalyst was measured and loaded into a fixed bed reactor. The temperature was raised to 300 °C at a rate of 5 °C / min and reduced in a H2 / N2 mixed atmosphere (volume ratio 1:9) for 3 h. Subsequently, the temperature was slowly lowered to 260 °C and the reaction was continued under normal pressure and a liquid hourly space velocity of 2.4 h -1 Under these conditions, anhydrous ethanol is metered into the reaction system at a constant flow rate. After vaporization at 300°C, it is carried by a carrier gas into the fixed-bed reactor, where a dehydrogenation reaction occurs under the action of the catalyst. Once the reaction stabilizes, the reaction product is sampled every hour and analyzed using a gas chromatograph.

[0047] The catalysts prepared in the above-mentioned Examples and Comparative Examples differ in the types and loadings of the copper and bismuth salts used. Their corresponding relationships are detailed in Table 1. The preparation process is essentially the same as in Example 1. The experimental test results of the catalysts prepared in the Examples and Comparative Examples for the dehydrogenation of ethanol to produce acetaldehyde are also shown in Table 1. As can be seen from Table 1, the catalysts prepared in the Examples exhibit significant advantages in terms of both selectivity and single-pass conversion, resulting in significantly higher single-pass yields than the Comparative Examples.

[0048] Table 1

[0049] Note: In Table 1, copper salts include copper acetate (Cu-1), copper nitrate (Cu-2), and copper chloride (Cu-3); bismuth salts include bismuth nitrate (Bi-1) and bismuth chloride (Bi-2); single-pass conversion = (amount of ethanol converted in a single reaction / amount of ethanol fed in a single reaction) * 100%; selectivity = (amount of ethanol converted to acetaldehyde in the reaction / amount of ethanol reacted) * 100%; single-pass yield = conversion * selectivity * 100%. It should be noted that the amount of ethanol mentioned in the activity indicators is in moles.

[0050] The experimental data from Examples 1-6 in Table 1 show that the catalytic performance is better when a copper acetate salt solution is used as the copper metal precursor. A comparison of Examples 1 and 2 reveals that a bismuth nitrate salt solution is used as the bismuth metal precursor, resulting in better catalytic performance. This suggests that the type of metal salt used in the active metal precursor influences the distribution and dispersion of active sites, and thus the catalyst activity level.

[0051] Further analysis of the experimental results of Example 1, Examples 7-12 and Comparative Examples 1-3 shows that the catalyst without bismuth salt is significantly less active; and when the amount of bismuth salt added is too much, some active sites will be occupied by bismuth, thereby destroying the synergistic effect between copper and bismuth metal, resulting in a decrease in acetaldehyde selectivity; the preparation method of the catalyst will also affect its catalytic activity. Comparative Examples 2 and 3 respectively use an impregnation method and a coprecipitation method to load the same active component as Example 1, which affects the dispersibility of copper. Its experimental results are better than those of the catalyst without bismuth loading, but the ethanol conversion rate and acetaldehyde selectivity are both lower than those of the catalyst of Example 1. In addition, as the active copper loading increases, the ethanol conversion rate is improved, but the amount of by-products generated also increases, which also leads to a decrease in acetaldehyde selectivity. Especially when the loading amount Cu: Bi = 5: 1 and the copper loading amount is in an appropriate range, the synergistic effect between copper and bismuth metal can more effectively suppress the agglomeration of the active component during the catalyst calcination process, improve the dispersibility of the catalyst, and ensure its stable and efficient activity level.

[0052] During catalyst stability testing, an appropriate copper loading range and copper-bismuth ratio were selected to control costs and reduce product separation difficulty. Given the long testing period, a 500-hour stability lifespan experiment was conducted on Examples 1, 3, and 5, as well as Comparative Examples 1, 2, and 3. The results are shown in Table 2. These results demonstrate excellent stability for Examples 1, 2, and 3, with conversion rate degradation of less than 5%, significantly lower than that of Comparative Examples 1-3.

[0053] Table 2

[0054] Note: In Table 2, conversion rate attenuation = initial conversion rate - conversion rate after attenuation.

[0055] To further investigate the long-term stability of the catalyst, Example 1 was selected for a 1500-hour stability test, with Comparative Example 1 used as a reference. The test results showed that during this period, the catalyst maintained a stable activity level and the conversion rate decay was less than 5%. Figure 5 The figure shows the changes in ethanol conversion and acetaldehyde selectivity during the stability test of Example 1 and Comparative Example 1, which allows a visual comparison of the stability differences between the two. The 5Cu / SiC catalyst prepared by the impregnation method in Comparative Example 1 shows that after a period of reaction, its ethanol conversion rate dropped from an initial 31.49% to 10.39%, and the acetaldehyde selectivity fluctuated greatly, which fully demonstrates that the catalyst deactivated quickly and the catalytic activity was unstable. In sharp contrast, the catalyst prepared in Example 1 showed a good ethanol conversion rate, and the acetaldehyde selectivity was stably maintained at above 90%, the reaction by-products were significantly reduced, and the average single-pass yield could reach 33%. In addition, the addition of the auxiliary agent metal bismuth effectively prevented the problems of copper metal agglomeration during calcination and copper carbon deposition deactivation during dehydrogenation, significantly enhanced the stability of the catalyst, and significantly improved its service life. In the stability test lasting up to 1500h, the catalyst of Example 1 showed no obvious signs of deactivation, the ethanol conversion rate and acetaldehyde selectivity remained stable, and the conversion rate attenuation was always less than 5%.

[0056] The above are preferred embodiments of the present invention. If ordinary technicians in this field are inspired by this and design structural methods and embodiments similar to the present technical solution without creatively designing them without departing from the purpose of the present invention, they should all fall within the scope of protection of the present invention.

Claims

1. A Cu-Bi bimetallic heterogeneous catalyst for dehydrogenation of ethanol to produce acetaldehyde, characterized in that: The Cu-Bi bimetallic heterogeneous catalyst includes a SiC carrier, and active components Cu and Bi supported on the SiC carrier; wherein the active component Cu loading is 3-15% of the total mass of the catalyst, and the active component Bi loading is 1-5% of the total mass of the catalyst.

2. The Cu-Bi bimetallic heterogeneous catalyst according to claim 1, characterized in that The particle size distribution of the SiC carrier is within the range of 2-50 nm.

3. The method for preparing the Cu-Bi bimetallic heterogeneous catalyst according to claim 1, characterized in that: The steps include: (1) performing high-temperature activation treatment on the SiC carrier to obtain an activated SiC carrier; (2) immersing the SiC carrier obtained in step (1) in a copper ammonia solution for ultrasonic impregnation, and then performing gradient ammonia evaporation; after the gradient ammonia evaporation is completed, filtering, washing and drying to obtain a Cu / SiC intermediate; (3) immersing the Cu / SiC intermediate obtained in step (2) in a bismuth salt aqueous solution for ultrasonic impregnation, and then filtering, washing and drying to obtain a bimetallic catalyst precursor; (4) The bimetallic catalyst precursor obtained in step (3) is calcined at a high temperature in an air atmosphere to obtain a Cu-Bi bimetallic heterogeneous catalyst.

4. The method for preparing the Cu-Bi bimetallic heterogeneous catalyst according to claim 3, characterized in that: In step (2), the specific process of gradient ammonia evaporation is as follows: after ultrasonic impregnation, the copper ammonia solution and the SiC carrier immersed in the copper ammonia solution are placed in an environment with a temperature of 40-60°C to evaporate ammonia for 1.5-2.5 hours, and then the temperature is raised to 75-85°C at a rate of 1-3°C / min, and ammonia evaporation is continued for 2-4 hours until the pH value of the copper ammonia solution is less than 8, and the gradient ammonia evaporation is completed.

5. The method for preparing the Cu-Bi bimetallic heterogeneous catalyst according to claim 3, characterized in that: In step (1), the method of high temperature activation treatment is: using air atmosphere, activation treatment at a temperature of 400-600°C for 1-10h.

6. The method for preparing the Cu-Bi bimetallic heterogeneous catalyst according to claim 3, characterized in that: In step (2), the copper ammonia solution is a copper ammonia complex solution formed by adding a copper salt into a solvent alcohol and dissolving it, then adding ammonia water to adjust the pH to 9-11 and continuously stirring; wherein the concentration of the copper salt in the alcohol is 50-300 mg / mL.

7. The method for preparing a Cu-Bi bimetallic heterogeneous catalyst according to claim 3, characterized in that: In step (2), the ultrasonic immersion time is 1-10 hours, and during the ultrasonic immersion process, the SiC carrier is completely immersed below the liquid surface of the copper ammonia solution.

8. The method for preparing the Cu-Bi bimetallic heterogeneous catalyst according to claim 3, characterized in that: In step (3), the concentration of bismuth ions in the bismuth salt aqueous solution is 0.01-0.06 mol / L, and the ultrasonic immersion time is 3-5 h.

9. The method for preparing a Cu-Bi bimetallic heterogeneous catalyst according to claim 3, characterized in that: In step (4), the specific process of high-temperature calcination is: the bimetallic catalyst precursor is calcined in an air atmosphere at a calcination temperature of 300-500° C. for 4-6 hours.

10. Use of the Cu-Bi bimetallic heterogeneous catalyst according to claim 1 in the dehydrogenation of ethanol to produce acetaldehyde, characterized in that: The Cu-Bi bimetallic heterogeneous catalyst is loaded into a fixed bed reactor and reduced in a mixed atmosphere of H2 and an inert gas at a reduction temperature of 200-550°C for a reduction time of 2-8 hours to obtain an activated catalyst; Under the conditions of normal pressure and temperature of 200° C.-350° C., ethanol is vaporized and carried by a carrier gas into a solid-phase bed reactor, where it is dehydrogenated to produce acetaldehyde under the action of the activated catalyst.